Perlindungan Hukum Bagi para Pihak dalam Perjanjian Jual Beli: Perbandingan Antara Kitab Undang-Undang Hukum Perdata dan Fikih Muamalah - Abd Rahman Saleh; Imam Fawaid (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze and compare legal protection for parties in a sale and purchase agreement based on the Civil Code (KUHPer) and Islamic law, using the fiqh muamalah approach. A sale and purchase agreement is a very common legal transaction in everyday life, so it is important to ensure legal certainty and justice for all parties involved. The research method used is normative-comparative with literature study techniques, which allows researchers to examine the differences and similarities in legal protection in both legal systems. The results show that in civil law, there is an emphasis on the principle of freedom of contract which gives space for the parties to determine the contents of the agreement according to their wishes, as long as it does not violate applicable laws and regulations. The formal form of the agreement is also an important aspect of legal protection, with regulations regarding default and fulfillment of performance that give the injured party the right to obtain compensation or fulfillment actions in accordance with the agreement. Meanwhile, Islamic law emphasizes the aspect of the lawfulness of the object of the sale and purchase, which must meet certain conditions for the transaction to be considered valid. Furthermore, in Islamic law, the consent or voluntary agreement of both parties is a primary requirement for a valid sale and purchase agreement to conform to the principles of substantial justice. While these two approaches differ philosophically and normatively, they share the same goal of protecting the rights and obligations of the parties involved in the sale and purchase agreement, thereby creating a fair transaction that does not disadvantage either party. The differences in approach between civil law and Islamic law are also evident in the dispute resolution mechanisms.